2020
DOI: 10.1126/sciadv.aba1933
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal mapping of neural activity and cerebral blood flow reveals long-lasting neurovascular dissociations after small-scale strokes

Abstract: Neurovascular coupling, the close spatial and temporal relationship between neural activity and hemodynamics, is disrupted in pathological brain states. To understand the altered neurovascular relationship in brain disorders, longitudinal, simultaneous mapping of neural activity and hemodynamics is critical yet challenging to achieve. Here, we use a multimodal neural platform in a mouse model of stroke and realize long-term, spatially resolved tracking of intracortical neural activity and cerebral blood flow i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 54 publications
2
57
0
Order By: Relevance
“…Future recordings will be required to determine the cortical extent of post pMCAo synchrony and whether it is pervasive in other stroke models including awake stroke models. An awake model of mini strokes found that spatiotemporal neuronal deficits extend beyond cerebral blood flow restoration in the days and weeks after ischemic onset 36 . Future studies should examine whether spatiotemporal synchrony extend in the long-term after pMCAo and if these neuronal network dynamics are related to residual blood flow dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Future recordings will be required to determine the cortical extent of post pMCAo synchrony and whether it is pervasive in other stroke models including awake stroke models. An awake model of mini strokes found that spatiotemporal neuronal deficits extend beyond cerebral blood flow restoration in the days and weeks after ischemic onset 36 . Future studies should examine whether spatiotemporal synchrony extend in the long-term after pMCAo and if these neuronal network dynamics are related to residual blood flow dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Another reason is related to technical limitations of ISI, which probably lacks the resolution to detect the activity of small numbers of neurons (scattered over a large cortical area or multiple layers) that exhibit compensatory plasticity (i.e., their signals are not sufficient to generate an ISI map). Alternatively, changes in blood flow and oxygen context after stroke (i.e., impaired neurovascular coupling (He et al, 2020)) may affect our ability to detect new ISI maps after stroke. To address these concerns about ISI, we also recorded whisker-evoked responses in the spared D3 barrel with in vivo 2P calcium imaging, which provides single cell resolution and is, in principle, impervious to changes in blood flow ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A number of previous studies from our lab and others has shown that focal cortical stroke leads to a long lasting dampening of cortical excitability and responsiveness to sensory stimulation that correlates with deficits in sensorimotor function of the affected limb 7,8,[32][33][34] . Based on the rationale that VIP interneurons could act as a dis-inhibitory circuit and thus potentially restore cortical responsiveness after stroke, we first characterized the effects of excitatory hM3Dq stimulation on VIP neurons in somatosensory cortex.…”
Section: Chemogenetic Stimulation Of Vip Interneurons Enhances Somatomentioning
confidence: 88%